Synthesis of hydrothermal alteration, rock mechanics and geophysical mapping to constrain failure and debris avalanche hazards at Mt. Ruapehu (New Zealand). Issue 2 (3rd July 2021) - Kereszturi, Gabor; Schaefer, Lauren; Mead, Stuart; Miller, Craig; Procter, Jonathan; Kennedy, Ben
ABSTRACT: Composite volcanoes can progressively weaken through hydrothermal alteration, which may lead to volcano collapse, forming far-reaching debris avalanches. This work reviews and synthesises the type and extent of hydrothermal alteration on Mt. Ruapehu, New Zealand, from rock mechanical, mineralogical, hyperspectral imaging and aero-magnetic studies for input into the first debris avalanche models of Mt. Ruapehu. Mt. Ruapehu shows surface weathering processes, forming goethite, hematite and phyllosilicate assemblages, and hydrothermally altered rock, with phyllosilicate, Fe- oxides and sulphates, pyrite, jarosite, alunite, anhydrite and sulphur. The surface alteration mapped by hyperspectral remote sensing is linked to the deep-seated (≤500 m) alteration by aero-magnetic inversion modelling. Textural analysis and mapping show that alteration weathering and porosity distribution are a result of the both the primary lithology, age, and location relative to active or fossil hydrothermal systems. The synthesis of the aero-magnetic data, previous magnetotelluric models, hyperspectral and hydrothermal mapping, and rock mechanics studies enabled the construction of a schematic model to provide inputs for modelling potential flank failure zones. These models suggest that the southwest and west flanks of Mt. Ruapehu have the highest probability of collapsing and generating debris avalanches.